Two decades of Open Access Campaigns: A Retrospective Analysis - Goveas, Jenice Jean; Sayer, Lizzie; Sud, Megha (Septentrio Conference Series, 2022)
At the start of this century, the Open Access movement gained momentum, largely fuelled by the Budapest (2002), Berlin (2003), and Bethesda (2003) declarations. The past two decades further witnessed several advocacy campaigns that challenged excessive profiteering through scientific publication, and advocated for revolutionising the scholarly publication system. Several attempts have been made to raise a voice for researchers’ rights that have been swallowed by the commercial publishing model. This study aims to give an overview of some major campaigns and organisations advocating for open access and analyses their efforts through the lens of their objectives, outcomes, opportunities, challenges and achievements. The assessment reveals some missing pieces that require careful consideration especially for current and future advocacy campaigns, as they are key building blocks of the Open Science movement. Such a mapping and understanding is crucial for sketching effective strategies needed to accelerate the progress towards achieving genuine and universal open access.